Strategi Pengelolaan Modal Kerja Dalam Meningkatkan Profitabilitas Dan Kemandirian UMKM Desa: Desa Pujon Kidul, Kecamatan Pujon, Kabupaten Malang - Ninda Rachmawati; Ayu Rachmawaty; Rosi Ani Prayekti; Fernando Aftha Prihandana; Devi Sabrina; Anesta Talica Femely (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Working capital management is an activity that includes all management functions of the company's current assets and short-term liabilities. The main objective of working capital management is to study and maintain an optimal balance among each component of working capital so that it can contribute to increasing profitability. This paper aims to conduct a study and theoretical review of the role of working capital management in an effort to increase profitability. A descriptive analysis was conducted to provide an overview of the understanding, benefits, and factors that affect working capital so that it can play a role in achieving profitability.